Respuesta :
Let us write down the equation and try to find one of the factors.
4x^2 + 5x - 6 = 0
4x^2 + 8x - 3x - 6 = 0
4x(x + 2) - 3(x + 2) = 0
(4x - 3)(x + 2) = 0
From the above deduction we can easily conclude that one of the factors of the equation given in the question is (4x - 3). The correct option among all the options that are given in the question is the fourth option or option "D".
4x^2 + 5x - 6 = 0
4x^2 + 8x - 3x - 6 = 0
4x(x + 2) - 3(x + 2) = 0
(4x - 3)(x + 2) = 0
From the above deduction we can easily conclude that one of the factors of the equation given in the question is (4x - 3). The correct option among all the options that are given in the question is the fourth option or option "D".